POLITENESS AS DIVINE IDENTITY IN THE QUR’AN: A RELIGIO-PRAGMATIC ANALYSIS OF FACE-SAVING IN PROHIBITIVE DISCOURSE - Saleh, Muhammad; Saputra, Dedi Gunawan; Sultan, Sultan; Basri, Muhammad Bahly (Universitas PGRI Sumatera Barat, 2025)
This study explores how Qur’anic prohibition discourse constructs divine-human identity through the lens of religio-pragmatics. While the Qur’an is often perceived as an authoritative and dogmatic text, this research argues that its prohibitive expressions also serve as instruments of moral education, relational harmony, and spiritual identity formation. The study uses a detailed examination of certain Qur’anic verses that include prohibitions, analyzing them through a politeness framework developed by Culpeper and Gillings, which has been adjusted. Findings reveal that Qur’anic prohibitions embody three interrelated modes of politeness that reflect the identity dynamics between the Divine and humanity. First, solidarity and politeness reinforce collective belonging by framing prohibitions as moral collaboration, “we” rather than “you,” fostering empathy and shared accountability. Second, tentative politeness manifests as instructive humility, softening imperatives through advisory tone, metaphor, and divine empathy, thereby shaping a compassionate religious self. Third, deferential politeness underscores the transcendent hierarchy between humans and God, in which linguistic restraint and acknowledgement of divine authority construct the believer’s humble identity before theCreator. These modes together form an Islamic model of divine politeness, in which prohibitions function not as coercive acts but as relational speech that guides, educates, and dignifies the interlocutor. Thus, Qur’anic language simultaneously performs theological instruction and identity negotiation, embedding moral values within pragmatic interaction. The study concludes that politeness in Qur’anic prohibitions is a face-saving system rooted in divine compassion, shaping both individual piety and communal harmony. It contributes to expanding pragmatic theory toward sacred discourse, illustrating how politeness becomes a theological act of identityconstruction within Islamic communication ethics.